Satisfaction of Iran’s Medical Students with Virtual Education in the Post-Pandemic era - Goudarzi, Amirreza; Khalili, Narjes; Haj-sheykholeslami, Arghavan (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2025)
This study aimed to assess medical students’ satisfaction with virtual education in Iran during the post-pandemic period. An online survey was conducted, involving 411 students (51.6% male; mean age: 22.7 ± 3 years) from 41 universities. The median proportion of education delivered via e-learning was 10%, with an interquartile range (IQR) of 5-20%. Students reported a median of two hours per week dedicated to e-learning (IQR: 1-7 hours). The average satisfaction score was 12.3 out of 20 (CI 95%: 11.9–12.7), with no significant differences observed based on gender, educational stage, or the region of the medical university.